What the Media Doesn’t See: Afghan and Syrian Labor in Turkey - Özgür Yılmaz (Obra Digital)
This study examines the portrayal of Afghan and Syrian migrants in Turkish media, focusing on the socio-economic and ideological dimensions of this representation. Through content analysis, the research highlights how media narratives often associate these migrants with crime and security concerns while overlooking their economic contributions, particularly in the informal labor market. The study underscores how such portrayals contribute to the marginalization and exclusion of migrants, perpetuating institutional racism. By critically analyzing these media depictions, the study calls for more balanced reporting and inclusive policy measures that recognize the contributions of migrant workers to Turkish society.